2021
DOI: 10.1097/mpg.0000000000003056
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fecal Incontinence in Children

Abstract: Functional fecal incontinence (FI) is a worldwide problem in children and comprises constipation-associated FI and nonretentive FI. Irrespective of pathophysiology, both disorders impact negatively on the psychological well-being and quality of life of affected children. A thorough clinical history and physical examination using the Rome IV criteria are usually sufficient to diagnose these conditions in most children. Evolving investigations such as high-resolution anorectal and colonic manometry have shed new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Fecal incontinence (FI), also known as encopresis or soiling, is one of the common gastrointestinal problems in children. It indicates the passage of the stool in the underwear by children four years of age and older who have completed toilet training (1). Initially, FI was considered only for children with neurological disabilities, but further studies showed that approximately one to four percent of four-year-old children (2) and one to two percent of children aged ten to sixteen years old experienced FI (3).…”
Section: Introductionmentioning
confidence: 99%
“…Fecal incontinence (FI), also known as encopresis or soiling, is one of the common gastrointestinal problems in children. It indicates the passage of the stool in the underwear by children four years of age and older who have completed toilet training (1). Initially, FI was considered only for children with neurological disabilities, but further studies showed that approximately one to four percent of four-year-old children (2) and one to two percent of children aged ten to sixteen years old experienced FI (3).…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [ 2 , 11 – 20 ]. Both constipation and fecal incontinence are addressed by the EP-DeFeC as these conditions often go together in children [ 17 , 28 ]. The bowel function scores facilitate the clinical interpretation of the questionnaire, because only counting fecal incontinence episodes or knowing stool frequency does not necessarily differentiate between children with acceptable bowel function and those in need of medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent causes of childhood constipation are improper toilet training and withholding behavior ( 5 ). Young toddlers experiencing painful defecation, such as from hard stools, have a natural instinct to retain their feces.…”
Section: Classification and Etiologymentioning
confidence: 99%
“…The basic treatment is the first-line treatment option of FI in children and adolescents. It has been reported that 22%–54% of patients with FI achieve a high QoL through diet, toilet training, and cognitive behavioral therapy ( 5 ).…”
Section: Management Of Fi In Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation